2018
DOI: 10.3390/met8080637
|View full text |Cite
|
Sign up to set email alerts
|

Transient Liquid Phase Bonding of Semi-Solid Metal 7075 Aluminum Alloy using ZA27 Zinc Alloy Interlayer

Abstract: Transient Liquid Phase Bonding (TLPB) process of semi-solid metal 7075 aluminum alloys (SSM7075) using 50 μm thick of ZA27 zinc alloys as interlayers for the experiment were carried out under bonding temperatures of 480 and 540 °C and bonding times of 30, 60, 90 and 120 min respectively. In the bonding zone, the semi-solid state of ZA27 zinc alloy interlayers were diffused into the SSM7075 aluminum alloy. Examination of the bonding zone using Scanning Electron Microscope (SEM) and Energy-dispersive X-ray spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Meengam el al. [6] investigated the possibility of using a ZA27 zinc alloy interlayer to bond 7075 aluminum alloy by TLP. The authors revealed that it was possible to obtain a sound dissimilar joint but the bonding time and temperature have a crucial influence on the microstructure interface that is an intimate bond with the mechanical properties of the joints.…”
Section: Contributionsmentioning
confidence: 99%
“…Meengam el al. [6] investigated the possibility of using a ZA27 zinc alloy interlayer to bond 7075 aluminum alloy by TLP. The authors revealed that it was possible to obtain a sound dissimilar joint but the bonding time and temperature have a crucial influence on the microstructure interface that is an intimate bond with the mechanical properties of the joints.…”
Section: Contributionsmentioning
confidence: 99%
“…Our idea is to bond this metal layer with the metal interconnect using the TLP process. TLP bonding is a well-known metallurgical joining process that has been tested on different metallic systems. , It works on the principle of the formation of a transient liquid phase, which reacts immediately to form intermetallic phases with higher melting temperatures. Typically, the metal combinations are chosen in such a way that one of the elements has a much lower melting temperature than the other.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the bonding temperature affects the amount of liquid fraction of solder formed during welding. Thereby, this could affect the formation of defects after welding [3] and is a foremost cause of bonded strength [4]. Likewise, the TLP diffusion bonding atmosphere is also necessary for welding.…”
Section: Introductionmentioning
confidence: 99%